Analisis Sentimen Masyarakat Terhadap Pemilihan Presiden Indonesia Berdasarkan Opini dari Media Daring: Sebuah Tinjauan Literatur - Mariana (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
This study aims to analyze information on sentiment analysis about related public sentiment on more specifically social media platform users about negative or positive sentiment towards the presidential election in Indonesia and generate new ideas for further sentiment analysis model research. The systematic literature review (SLR) method is used to review and synthesize research data. This study proposes a sentiment analysis model for Indonesian text using the long short-term memory network (LSTM) method with preprocessing methods, namely transformation, tokenization, stop word removal, lemmatization, and post tagging.